PENANGANAN KASUS KECELAKAAN LALU-LINTAS DENGAN ANAK SEBAGAI PELAKU DI WILAYAH POLRES KUDUS - Haryono; Hidayatullah (Judge : Jurnal Hukum, 2026)
Traffic accidents involving children as perpetrators require special handling that prioritizes child protection and the principles of restorative justice. This study aims to analyze the handling of traffic accident cases involving children as perpetrators and to examine the implementation of diversion, discretion, and restorative justice within the juvenile criminal justice system as an effort to provide legal protection. The research employs a normative juridical method with a descriptive approach through the analysis of legal literature. The findings indicate that the application of diversion and discretion based on restorative justice constitutes an important instrument in the juvenile criminal justice system to ensure legal protection and achieve substantive justice without disregarding the child’s criminal responsibility. Diversion is carried out through deliberation or mediation mechanisms as a form of case resolution outside the formal criminal justice process, oriented toward restoring the original condition in a humane and non-formal manner.